A review of the genera Atracodes Melichar and Pseudoflatoides Metcalf (Hemiptera: Flatidae: Flatoidinae) from the Caribbean region - Levia, Nathaniel N.; Bartlett, Charles R. (Zootaxa, 2025)
The genera Atracodes Melichar, and Pseudoflatoides Metcalf, are small Antillean genera in the flatid subfamily Flatoidinae. We found Pseudoflatoides to be a junior subjective synonym of Atracodes resulting in the transfer of four species (and seven subspecies). We revise the status of two subspecies of Atracodes fasciculosus comb. nov. to species level (as Atracodes fasciatus comb. nov. & stat. nov. and Atracodes vittatus comb. nov. & stat. nov.) based on characteristics of the male terminalia. Atracodes corrugatus Melichar (from Madagascar) is transferred to Lichenopsis Schmidt as Lichenopsis corrugata (Melichar), comb. nov. The resulting composition of Atracodes is 10 species, and four subspecies. We also compile available information on the two genera, provide a key to the American genera of Flatoidinae, along with a key to species of Atracodes, and suggest future work on the subfamily.